A discourse study of silence in selected political speeches - Hussein, Azhar Mohammed; Ahmed, Muayyad Naji; salman, dinamoh ammed (International Journal of Psychosocial Rehabilitation, 2020)
Politics is said to be a game of maneuverings and part of that is the use of silence as a means of communication. This may sound strange as communication itself connotes the art of expression. However in politics, a political figure may choose to remain silent as a means of passing a message across to the public in a trouble situation when he is expected to make a comment. This research paper tackles that whereas this strategy works well in some instances it fails in other instances. It, therefore, recommends that politicians should be cautious in the use of strategic silence as a means of political communication in view of the nature of politics which calls for self- expression in the use of persuasion, clarification and conviction to win public support and sympathy. Maintaining silence when one is most expected to speak out could easily be misunderstood as a sign of incompetence, intransigence or outright arrogance by the public. This research paper is divided in to three sections; the first section is an introduction to the problem, aims of the study, limits and procedures of the study. The second section introduces the concept of silence, its features, types, functions and an important theory in which is the spiral of silence. Section three contains all the conclusions the study has arrived at and the referenced used.